Residual Governance How South Africa Foretells Planetary Futures - Hecht, Gabrielle (Duke University Press, 2023)
Diving in to the history of South African gold and uranium mining, Gabrielle Hecht shows how forms of state governance and the fight for infrastructural and environmental justice tell a global story of racial capitalism and the Anthropocene.